2014
DOI: 10.1002/cctc.201402500
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Driven Alcohol Dehydrogenation with a Rhodium Catalyst

Abstract: We report the photocatalytic dehydrogenation of alcohols with a Rh catalyst and I− in an acidic medium. The catalyst screening of a structurally diverse family of Rh complexes found [RhIII(dtbbpy)2(OSO2CF3)2](CF3SO3) (Rh7; dtbbpy=4,4′‐di‐tert‐butyl‐2,2′‐bipyridine) to be the best catalyst. All components (Rh7, HI, alcohol, and light) were found to be essential for the dehydrogenation to occur. Under optimal conditions, generation of both H2 and acetone (for isopropyl alcohol) was observed, which increased line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 111 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…It must be pointed that the presence of a noble metal as co-catalyst is necessary for alcohol dehydrogenation [22,23]. Recently, the possibility of alcohol dehydrogenation by complexes of noble metals has been reported [24,25].…”
Section: Photocatalyst Preparationmentioning
confidence: 99%
“…It must be pointed that the presence of a noble metal as co-catalyst is necessary for alcohol dehydrogenation [22,23]. Recently, the possibility of alcohol dehydrogenation by complexes of noble metals has been reported [24,25].…”
Section: Photocatalyst Preparationmentioning
confidence: 99%
“…The only by‐product, hydrogen, is a sustainable energy carrier due to its high energy capacity [8–9] . It is worth noting that high selectivity of aldehydes or ketones can be achieved in this approach owing to the absence of oxidants [10–32] …”
Section: Introductionmentioning
confidence: 99%
“…Alcohol splitting is an uphill reaction (endothermic), implying that energy is required to drive this reaction [10–32] . Conventional alcohol splitting reactions are usually conducted at equal or above 90 °C [10–24] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37] Very recently, we have found that Cu(I) pyrimidine-2-thiolate clusters can efficiently catalyze transfer hydrogenation reactions via a cooperative metal hydride and ligand proton transfer mechanism. 38 Cu(I) N-heterocycle thiolate clusters are potentially attractive precursors for the construction of bifunctional photocatalyst MOFs based on the following considerations: (i) metal thiolate complexes can be used as co-catalysts for the production of hydrogen compatible with a photosensitizer, [39][40][41][42][43][44][45] (ii) Cu(I) Nheterocycle thiolates absorb visible light and are intensely luminescent with long uorescent lifetimes, [46][47][48] (iii) they can smoothly achieve such conversion at 100 C, 38 Single-crystal analysis revealed that 2 crystallized in the tetragonal space group P4 1 2 1 2, 3 crystallizes in the monoclinic space group C2/c. In 2, each "Cu 6 (dmpymt) 6 " unit is interconnected with the other four through "Cu 2 (m-I) 2 " linkages forming a 2D layer, which is further connected to equivalent layers via N-Cu-N bonds to form a 3D net (Fig.…”
Section: Introductionmentioning
confidence: 99%